(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
Preeclampsia is a severe pregnancy-related disorder that significantly impacts multiple organ systems, with the kidneys being among the most affected. This study aims to analyze the pathomorphological changes in the kidneys of pregnant women who succumbed to preeclampsia, highlighting the structural and functional impairments associated with the condition.